2018
DOI: 10.1371/journal.pone.0196734
|View full text |Cite
|
Sign up to set email alerts
|

High-dose versus standard-dose amoxicillin/clavulanate for clinically-diagnosed acute bacterial sinusitis: A randomized clinical trial

Abstract: BackgroundThe recommended treatment for acute bacterial sinusitis in adults, amoxicillin with clavulanate, provides only modest benefit.ObjectiveTo see if a higher dose of amoxicillin will lead to more rapid improvement.Design, setting, and participantsDouble-blind randomized trial in which, from November 2014 through February 2017, we enrolled 315 adult outpatients diagnosed with acute sinusitis in accordance with Infectious Disease Society of America guidelines.InterventionsStandard-dose (SD) immediate-relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…power to detect an increase of 18 percentage points in the GRI among those in the high-dose group (ie, an increase to 52%, as reported previously 5 ) with an α of .05 for a 2-sided test. We aimed, therefore, to enroll 240 patients (anticipating 10 dropouts before day 3).…”
Section: Sample Sizementioning
confidence: 57%
See 3 more Smart Citations
“…power to detect an increase of 18 percentage points in the GRI among those in the high-dose group (ie, an increase to 52%, as reported previously 5 ) with an α of .05 for a 2-sided test. We aimed, therefore, to enroll 240 patients (anticipating 10 dropouts before day 3).…”
Section: Sample Sizementioning
confidence: 57%
“…A double-blind, placebo-controlled trial was performed from 2014 to 2017 comparing high-dose and standard-dose amoxicillin with clavulanate for adults with clinically diagnosed acute bacterial sinusitis. 5 That study confirmed that very few individuals carried resistant bacteria. The primary outcome was the participants’ subjective rating of improvement after 3 days of treatment, knowing that most people get better by 2 weeks but value rapid relief and that the benefit of other common treatments—eg, for streptococcal pharyngitis 6 and influenza 7 —is largely a quicker improvement.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…1 Amoxicillin is used as an effective and safe therapy for sinusitis, otitis media, acute exacerbations of chronic bronchitis, epiglottitis, urinary tract infections, meningitis, and salmonella infections. [2][3][4] In India, a previous study reported that 1.78% of adverse reactions reported due to amoxicillin + clavulanate of 4.99% of total ADRs among pediatric patients, the ADRs include hypersensitivity reactions: angioedema, anaphylaxis, mild fever, rash, purpura, lymphadenopathy, generalized oedema, albuminuria, and hematuria. 5 Cutaneous adverse reactions like skin rashes, urticaria, itching, fixed drug eruption, angioedema are the common among the various adverse drug reactions (ADR).…”
Section: Introductionmentioning
confidence: 99%